Justification for choosing of grinding wheel options and grinding modes - Lapenko, H.; Yakhin, S.; Lapenko, T.; Pavlyk, O. (Scientific Progress & Innovations, 2022)
Grinding is one of the final types of processing, which provides high quality of the treated surface (accuracy and roughness) at high productivity of the process. Ensuring the properties of the surface depends largely on the correct choice of the working tool – the grinding wheel, and the parameters of the grinding mode. The main characteristics of the grinding wheel are its geometric parameters (diameter, width) and the characteristics of the material of the wheel (grain size, binder type, diamond concentration and thickness of the diamond layer). The parameters of the grinding mode include the speed of rotation of the wheel and the depth of grinding and feed. Premium and CBN grinder wheels on the organic connection of the production of PJSC “Poltava Diamond Tool” are used in the study. The parameters for the grinding round as well as the grinding modes have been chosen based on DSTU (ISO), which regulates the nomenclature of grinding round and requirements of how they should operate: the roughness of a finished surface – Ra and the coefficient of grinding. We considered and analysed constant parameters, like the brand of grinding circle, the type of grinding operation (flat) and the use of lubricating and cooling technical means, as well as variable parameters of grinding mode. The parameters of the grinding mode are the main control factors of the grinding process and are set for the grinding machine by the operator directly. PJSC “Poltava Diamond Tool” is the company that specialises in the production of a wide range of diamond and CBN tools for grinding and polishing hard alloys, as well as heat-resistant, alloyed and stainless types of steel and other materials. The specialists of the factory together with scientists have carried out multiple works on optimising the method of choosing the grinding parameters and the grinding mode depending on the processing material, the specified accuracy and roughness of the surface and working capacity. The recommended range of grinding wheel grain and relative concentration of diamond powder in the diamond layer has been developed to achieve the specified roughness of the treated surface at different types of grinding. The recommended grinding modes are presented for different types of grinding with circles from cubic boron nitride CBN.